Minat Generasi Muda Terhadap Kesenian Tari di Desa Kuala Merbau Kabupaten Kepulauan Meranti - Laila Luqyana; Muhammad Fikri; Firdaus Firdaus; Syielvi Dwi Febrianty (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the condition of youth interest in dance arts and the factors that hinder youth interest in dance arts in Kuala Merbau Village, Pulau Merbau District, Kepulauan Meranti Regency. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results showed that youth interest in dance arts is relatively low, as indicated by declining participation, irregular training activities, and reduced involvement in cultural art activities. The factors inhibiting youth interest include limited facilities and infrastructure, a shortage of dance instructors and art administrators, financial constraints, the influence of gadgets and social media, the social environment, and the lack of cultural art activities in the village. The study concludes that the low interest of young people in dance arts is influenced by various interrelated factors, requiring collaborative efforts to preserve dance arts as part of local cultural heritage.